THE CHALLENGES AND STRATEGIES IN TEACHING READING: AN INSIGHT INTO TEACHERS’ VOICES - Alviaderi Novianti; Martina Mulyani; Putri Febriani (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2021)
This research aimed at revealing teachers’ challenges in teaching reading and their strategies used to overcome those challenges. To fulfil those aims, the researcher used descriptive qualitive as this research method, and collect the data by spreading questionnaire and conduct semi-structured interview. Ten English teachers were involved as research sample. They were not only given questionnaire deal with the challenges in teaching reading, but also interviewed regarding to the strategies their used to overcome those challenges. From the data gathered, it revealed that the challenges mostly originated from students’ lack of vocabulary mastery and their motivation to actively involved in classroom participation. Regarding to those problems, the teacher then used some strategies including brainstorming and pair works. In fact, however, those strategies could help the teacher in engaging the students in teaching reading.